LINGUISTIC SIGNIFICANCE OF THE CONCEPT OF “WEALTH” IN ENGLISH AND UZBEK PROVERBS AND SAYINGS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article is dedicated to the comparative analysis of paremiological representing the concept of “Wealth” in English and Uzbek languages. Special attention was paid to the terms of concept, and Proverbs. The topic was explained by analysis of some English and Uzbek proverbs regarding the concept of “Wealth”.